Knowledge, Attitude, And Practices On Infection Control During Dental Missions of Dentists Of A Philippine Dental Association Dental Chapter In Metro Manila/Abiel Grace G. Sales. - Sales, Abiel Grace G. Author; Ong-Sedilla, Ranee Nicole (2021)
INTRODUCTION: In the Philippines, dental missions give dental care and instruction to unreached areas. In dental missions, infections control may not be as good as it is in a dental clinic because of the nontraditional setting. This study examines dentists' knowledge, attitudes, and practices about infection control methods, as well as the form, type, and underlying factors that influence them.
METHODS: Through simple convenience sampling of the Philippine Dental Association (PDA) chapter in Metro Manila, self-administered survey questionnaires on infection prevention during dental missions were delivered to 124 practitioners. Dentists agreed to participate in an interview and discuss their experiences. All the information gathered was analyzed and presented using descriptive statistics.
RESULTS: The findings suggest that the PDA Chapter has established infection management guidelines, of which 45.2%of the participants are aware. The average knowledge of infection control during dental missions is held by 51.6% of respondents. Among the respondents, 48.4% have good practices, while 34.7% have excellent practices, while overall maintaining a positive attitude to those practices. Liquid disinfection is most prevalent from infection control utilized during dental missions having suitable PPE and access to sterilizing equipment are the two most important elements determining the quality of infection control during dental missions.
CONCLUSIONS: During dental missions, the respondents demonstrated substantial knowledge, attitude, and practices regarding infection control, and they were aware of existing infection control protocols. Adherence to these infection control methods is multifaceted, and it must be addressed appropriately in order to comply with tight infection control protocols to the maximum level and in accordance with guidelines specifically for dental missions in the Philippines.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental mission; Infection--Prevention and control